Three-dimensional-printed malo bridge: Digital Fixed prosthesis for the partially edentulous maxilla - A A Ponnanna; Subhabrata Maiti; Nitesh Rai; P Jessy (Wolters Kluwer Medknow Publications, 2021)
Screw-retained implant restorations have an advantage of predictable retention, retrievability, and lack of potentially retained subgingival cement. However, a few disadvantages exist such as need for precise placement of the implant for optimal and esthetic location of the screw access hole and obtaining passive fit. Malo bridge with customization of abutment can establish a precise patient's gingival architecture. It is the most esthetically advanced form of fixed prosthodontic rehabilitation for complete and partially edentulous patients. This prosthesis is combined with three-dimensional (3D)-printed computer-aided design and computer-aided manufacturing technology to gain the precise fit and added esthetics. It also has advantages such as elimination of screw access openings, makes it possible to remove and repair the fractured porcelain of the individual crown without removing the whole structure, excellent precision, avoids casting errors, light weight, reduced complexity of laboratory procedures, high definition of morphology, and time-consuming. This case report presents replacement of partially edentulous maxilla using 3D-printed Malo bridge.